Selection of oviposition sites by ground beetles Abaris basistriata and Selenophorus seriatoporus for mass rearing purposes - Barbosa-Andrade, Crislany L. [UNESP]; Andrade, Daniel J. [UNESP]; Matos, Sidnéia T. S. [UNESP]; Nogueira, Luciano [UNESP]; Cividanes, Francisco J. [UNESP] (Springer Nature, 2019)
The oviposition preferences of Abaris basistriata Chaudoir and Selenophorus seriatoporus Putzeys (Coleoptera: Carabidae) were studied in the laboratory. Tested variables were substrate type (soil, vermiculite, cotton wool, and black gauze) and soil depth (0 to 20 cm) in terms of carabid beetle preference for oviposition. Both carabids preferred soil over the other substrates for oviposition. However, A. basistriata also showed a preference for black gauze. As for oviposition depth, A. basistriata laid eggs at a depth of 12 cm, while S. seriatoporus up to 20 cm. In terms of cost, soil was unprofitable as a substrate, mainly due to a high labor demand for prior preparation. Cotton wool was the substrate with the lowest cost. In conclusion, preference is a key mechanism that has to be understood the rearing ground beetles.
Keywords: Biological control; Breeding behavior; Carabidae; Coleoptera; Laboratory rearing; Production costs